Analisis Perbandingan Kinerja Keuangan Sebelum Dan Saat Masa Pandemi Covid-19 - Keziah Frydha Putri Arwantini; Syaiful Syaiful (Journal of Culture Accounting and Auditing, 2022)
This research aims to find out and perfome analysis a comparative analysis of the financial performance of food and beverage companies listed on the Indonesia Stock Exchange before and during the Covid-19 pandemic. This research uses quantitative research with comparative descriptive method. The data analysis technique uses Profitability Ratios as measured by Return On Assets, Liquidity Ratios as measured by Current Ratios, Solvency Ratios as measured by Debt to Equity Ratios, and Activity Ratios as measured by Total Assets Turnover. This study uses 64 data of company financial statements listed on the Indonesia Stock Exchange in 2018-2021. The test is carried out using a different test. The test results show that there are no significant differences in the Return On Assets and Current Ratios before and during the COVID-19 pandemic, while there are significant differences in the Debt to Equity Ratio and Total Assets Turnover before and during the COVID-19 pandemic.